Blogs and narratives in education: Deciphering me - Iop, Maria Cristina Rigão; Rigão, Maria Helena (Seven Editora, 2023)
Using as a theoretical basis the paradigm of complexity, supported by authors such as Humberto Maturana, Francisco Varela and Edgar Morin, I propose some reflections from an activity with narratives for the recovery of the author subject. The intention was to disturb young people through the use of blogs, involving self-experience and autonomy, so that they build knowledge/subjectivity in an inseparable way, considering the human/machine coupling. The narratives show the process of self-constitution and cognition emerging together, through the production of meanings for living, reconfiguring their life history and raising their level of complexity. As I get involved in the process, I start thinking about everyone involved, the emotion comes in, and then I start learning. The narratives allow us to make a reading of emotions, enchantment, learning and understanding. It is an awareness of oneself, of the process of living, of social interactions. It is a construction that takes place in a process of reflection, because educating is the process of living with the other and transforming oneself in a reciprocal way. We are educated in educating. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-107